DISSOLUTION TEST IN QUALITY ASSESSMENT OF TABLETS CONTAINING 11-DEOXYMISOPROSTOL - A. A. FEDOTOVA; A. G. YALKAEV; V. A. KATAEV; R. A. KHALIKOV; F. Kh. KILDIYAROV (Кубанский научный медицинский вестник, 2018)
Aim. Development of the dissolution test method of 11-deoxymisoprostol tablets.Materials and methods. The research was carried out on a "paddle apparatus". The media dissolution temperature is 37±0,5 degrees, the stirring rate is 50 rpm, the sampling time is 45 minutes, the dissolution media volume is 500 ml. The method of quantitative determination of 11-deoxymisoprostol in sample solution – HPLC with UV-detection, reverse phase chromatography. Chromatograph "Shimadzu Prominence LC-20" (Japan) with a matrix photodiode detector SPD20, column Discovery C18 (5 μm; 150 mm x 4.6 mm), mobile phase: water-acetonitrile (50:50), isocratic elution, detection at a wavelength of 195 nm.Results. All tested tablet samples meet the requirements of the State Pharmacopoeia in terms of "Dissolution test".Conclusion. A dissolution test method of 11-deoxyimisoprostol tablets has been developed.